Reliability Analysis Method of the Motion Accuracy of Rotating Guide-bar Mechanism Considering Multi-correlated Failure Mode - Li Chang; Wang Bingchen; Han Xing; Song Hua (Jixie chuandong)
There inevitably existed multi-correlated failure modes in the mechanism motion process,and these modes are expressed as functions of random variables.Firstly,a reliability calculation model for the mechanism motion under multi-failure mode is built and solved.Secondly,taking the rotating guide-bar mechanism as example,the calculation solution of the motion accuracy reliability under multi-correlated failure mode is carried out based on the method of Monte Carlo.Lastly,the guide-bar mechanism reliability curves under different times are got,and the theory foundation for mechanism dynamic optimum design is provided.This method with high accuracy,has some theory meaning and application value.